The Neutralized Lever: Exchange Rate Stability and the Paradox of Growth in Post-conflict Iraq (2005-2024) - Dilgash Ahmed Mohammed (Shirkah: Journal of Economics and Business, 2025)
In Iraq's post-conflict, oil-dominated economy, achieving macroeconomic stability is paramount, with the exchange rate acting as a central, yet complex, determinant of growth. This study empirically dissects the long-term relationship between exchange rate stability and economic growth from 2005 to 2024. Analyzing time-series data from the World Bank, IMF, and Central Bank of Iraq, the study applied a multiple linear regression model, robustly supported by unit root (ADF) and Johansen cointegration tests, to assess the impact of currency stability alongside foreign direct investment (FDI), inflation, trade openness, oil revenue, and political stability. The Johansen cointegration test confirms that a stable long-run equilibrium exists among the variables. However, our findings reveal a critical paradox: while the regression model explains a substantial 80% of the variation in GDP growth (R² = 0.80), no individual predictor is statistically significant. This outcome highlights how Iraq’s deep-seated structural challenges, overwhelming oil dependency, political instability, and potential multicollinearity, overshadow and neutralize the independent effects of conventional policy levers. Consequently, while exchange rate stability shows a positive but statistically insignificant effect, it is not a silver bullet for growth. This research concludes that sustainable economic recovery in Iraq is contingent not merely on currency management but on a foundational shift towards comprehensive institutional reforms, aggressive economic diversification, and integrated macroeconomic policies.